Integrating Fintech, CSR, and green finance: impacts on financial and environmental performance in China - Xianghua Yuan (Humanities & Social Sciences Communications)
Abstract This study, grounded in the Resource-Based View (RBV) theory, investigates the impact of Fintech Adoption (FA) on Financial Performance (FINP) and Environmental Sustainability Performance (ESP) in Chinese banking institutions, with a focus on the mediating roles of Corporate Social Responsibility (CSR) and Green Finance (GF). Using a combination of statistical analysis techniques, including Structural Equation Modeling (SEM) and Necessary Condition Analysis (NCA), this study analyzed data from 257 banking professionals. The empirical findings reveal that FA significantly enhances FINP, ESP, CSR, and GF, with the greatest effect on the effectiveness of GF initiatives. This underscores the critical role of Fintech in both financial growth and environmental sustainability within the banking sector. However, the study also found that the direct impact of CSR on FINP was not significant, highlighting an area for further exploration. The NCA analysis further emphasized that FA and ESP are key drivers for improving financial performance, emphasizing Fintech’s strategic value in maintaining a competitive edge. This study contributes to the understanding of Fintech’s broader impact, offering practical insights for policymakers and industry practitioners on integrating technological innovation with sustainable banking practices. The findings suggest that banking institutions can leverage Fintech to enhance both financial and environmental outcomes, while policymakers should foster regulations that support such integrations for a sustainable future.